Intra-aortic balloon pump (IABP) counterpulsation improves cerebral perfusion in patients with decreased left ventricular function. (November 2014) - Pfluecke, C; Christoph, M; Kolschmann, S; Tarnowski, D; Forkmann, M; Jellinghaus, S; Poitz, DM; Wunderlich, C; Strasser, RH; Schoen, S; Ibrahim, K
Background: The current goal of treatment after acute ischemic stroke is the increase of cerebral blood flow (CBF) in ischemic brain tissue. Intra-aortic balloon pump (IABP) counterpulsation in the setting of cardiogenic shock is able to reduce left ventricular afterload and increase coronary blood flow. The effects of an IABP on CBF have not been sufficiently examined. We hypothesize that the use of an IABP especially enhances cerebral blood flow in patients with pre-existing heart failure. Methods: In this pilot study, 36 subjects were examined to investigate the effect of an IABP on middle cerebral artery (MCA) transcranial Doppler (TCD) flow velocity change and relative CBF augmentation by determining velocity time integral changes (ΔVTI) in a constant caliber of the MCA compared to a baseline measurement without an IABP. Subjects were divided into two groups according to their left ventricular ejection fraction (LVEF): Group 1 LVEF >30% and Group 2 LVEF ≤30%. Results: Both groups showed an increase in CBF using an IABP. Patients with a LVEF ≤30% showed a significantly higher increase of ΔVTI in the MCA under IABP augmentation compared to patients with a LVEF >30% (20.9% ± 3.9% Group 2 vs.10.5% ± 2.2% Group 1, p<0, 05). The mean arterial pressure (MAP) increased only marginally in both groups under IABP augmentation. Conclusions: IABP improves cerebral blood flow, particularly in patients with pre-existing heart failure and highly impaired LVEF. Hence, an IABP might be a treatment option to improve cerebral perfusion in selected patients with cerebral misperfusion and simultaneously existing severe heart failure.